Religious conviction in liberal politics - Eberle, Christopher J. (Cambridge University Press, 2002)
"Is it possible for a deeply religious person to be a good citizen in a liberal democracy? There is room for doubt regarding many religious believers. Why? Many religious people take themselves to be conscience bound to support coercive laws for which they have only religious reasons. But many political theorists claim that such exclusive reliance on religious reasons violates the norms of good citizenship and does so for any of a number of reasons: It grinds to a halt productive conversation on the laws to which we are subject: it injects gratuitously divisive factors in already overheated discussions; it fails to respect the autonomy and personhood of citizens who find religious reasons implausible."